Teachers’ perception on COVID-19 vaccination and preventive behaviour in Denpasar, Bali - Sridyantari, Luh Verra; Sawitri, Anak Agung Sagung; Putra, I Wayan Artawan Eka (Universitas Udayana, 2022)
Background and purpose: Teachers as one of the public service providers are at risk of transmitting or contracting COVID-19, so they are prioritized to get COVID-19 vaccination. This study aims to explore teachers’ willingness to vaccinate, their behaviour and perception after COVID-19 vaccination. Methods: We conducted a cross-sectional study involving 200 teachers from 20 primary and secondary schools in Denpasar, who were selected by stratified multistage random sampling. The variables collected are sociodemographic characteristics (age, gender, religion, education, economic status), willingness to be vaccinated, behaviour after the vaccination, and the beliefs which include perceived vulnerability, perceived seriousness, and perceived benefits. Data analysis was carried out descriptively to describe the behaviour and perception of teachers after the vaccination. Results: Most teachers were middle-aged (31-45 years) and female (74%), with undergraduate education (84%). Most of the respondents were willing to be vaccinated and had been vaccinated (97%). Respondents had a low vulnerability belief of 18%, a high seriousness belief of 8.5% and a low benefit belief of 3.5%. All teachers have intentions to continue implementing health protocols to prevent transmission of COVID-19. Conclusion: Some school teachers have low perceived vulnerability, high seriousness, and belief of low benefits after vaccination. This shows that teachers are still unsure about the COVID-19 vaccine effectiveness in preventing the transmission of COVID-19, so further education effort is needed.